Prevalence of Cow Milk Protein Allergy among Libyan Asthmatic Children - Soad Alhadi,; Ola Elzigallai,; Hisham Alrabty, (AlQalam Journal of Medical and Applied Sciences, 2025)
Coexistent food allergy and asthma is a significant burden in the pediatric population, and the incidences of both have increased dramatically over the past two decades. Cow milk protein allergy is the most common allergy in children with prevalence between 1.8% and 7.5% during the first year of life. The variability between studies may be attributable to different methods used for diagnosis, the different ages of the populations studied or to geographical factors. The purpose of this study is to determine the prevalence and clinical impact of cow milk protein allergy in Libyan asthmatic children. This was a crosssectional study done between December 2021 and December 2022 at Tripoli children hospital. The study included 200 asthmatic children who regularly attending the childhood asthma clinic. Detailed questionnaire was used, and data were analyzed using SPSS and presented as descriptive statistics. Out of 200 asthmatic children included, 10% of them had cow milk protein allergy, their mean age was 2.7± 2.6years, and about 80% of cases were below 5 years of age (P < 0.05). Furthermore, our findings exhibited significant association between family history of atopy and cow milk protein allergy (P < 0.05). About 45% of asthmatic cases were affected by cow milk protein allergy, of which 5% of them had progressive course. Future studies should aim to include larger samples of cow milk protein allergy cases, which allow sufficient statistical power to uncover the epidemiology of this allergy. تشكل حساسية الطعام والربو المتزامنين عبئًا كبيرًا على الأطفال، وقد زادت حالات الإصابة بكليهما بشكل كبير على مدى العقدين الماضيين. تعد حساسية بروتين حليب البقر أكثر أنواع الحساسية شيوعًا لدى الأطفال مع انتشار يتراوح بين 1.8٪ و 7.5٪ خلال السنة الأولى من العمر. قد يُعزى التباين بين الدراسات إلى الأساليب المختلفة المستخدمة للتشخيص، أو الأعمار المختلفة للسكان الذين تمت دراستهم أو إلى العوامل الجغرافية. الغرض من هذه الدراسة هو تحديد انتشار وتأثير حساسية بروتين حليب البقر السريري لدى الأطفال الليبيين المصابين بالربو. كانت هذه دراسة مقطعية أجريت بين ديسمبر 2021 وديسمبر 2022 في مستشفى طرابلس للأطفال. شملت الدراسة 200 طفل مصاب بالربو يرتادون عيادة الربو للأطفال بانتظام. تم استخدام استبيان مفصل، وتم تحليل البيانات باستخدام برنامج SPSS وتقديمها كإحصائيات وصفية. من بين 200 طفل مصاب بالربو، كان 10٪ منهم مصابين بحساسية بروتين حليب البقر، وكان متوسط ​​أعمارهم 2.7 ± 2.6 سنة، وكان حوالي 80٪ من الحالات أقل من 5 سنوات (P < 0.05). وعلاوة على ذلك، أظهرت نتائجنا وجود ارتباط كبير بين التاريخ العائلي للحساسية وحساسية بروتين حليب البقر (P < 0.05). تأثر حوالي 45٪ من حالات الربو بحساسية بروتين حليب البقر، وكان 5٪ منهم لديهم مسار تقدمي. يجب أن تهدف الدراسات المستقبلية إلى تضمين عينات أكبر من حالات حساسية بروتين حليب البقر، مما يسمح بقوة إحصائية كافية للكشف عن علم الأوبئة لهذه الحساسية